Doktrin Manusia Dan Dosa - Dini; Nazareth Dealova; Rorin April Nadiya; Sarmauli (CV Edujavare Publishing, 2024)
Talking about the fall of man into sin is a very hot topic discussed by theologians to this day. It is still a mystery, leaving many questions in the head about the origin of sin and why God allowed it to happen and how humans get out of it. This is what makes people still debate to know the answer with their own interpretation to find the truth. As a result of this research, it was found that the origin of sin is the origin of the first human disobedience, namely Adam and Eve to God. And the only way out for humans from sin is Jesus Christ sacrificing himself on the cross to atone for human sin.